"Razgleduj se po velikem mestu, katerega nisi še nikdar videl ---" - Smolej, Tone (Jezik in slovstvo, 2002)
"Look around the big city you have never seen ..." Images of France in Janez Cigler's texts. In Janez Cigler's story Sreča v nesreči France features as a godless country, in which the main character, a Slovene man, simply has to preserve his Christian belief to survive the many dangers threatening him in the unfamiliar environment. While Cigler disapproved of the secularisation of French society, he was fascinated by some French cities. In his story Deteljica the main character thus spends a considerable amount of time strolling around Paris and admiring its sights. Both stories also portray the French army in its ignominious defeat.
Keywords: Cigler, Janez, 1792-1867; Slovene literature; slovenska književnost; literarne študije; France; Francija; Cigler, Janez: Sreča v nesreči ali Popisovanje čudne zgodbe dveh dvojčkov; slovenska literarna zgodovina